Urban air dispersion model of a mid-sized city. Validation methodology - Silva, Lígia Torres (2010)
Viana do Castelo is a mid-sized city located on the northwest Portuguese seaside, which undertook the challenge of developing an environmental program leading to the integration in the Healthy Cities European Network. Within this program includes prediction of pollutant concentration for NO2, CO, PM10, O3 and C6H6. This paper presents the methodology developed to validate the modelled results. Predicted concentrations were compared against measured concentrations of a chosen pollutant: Carbon Monoxide, CO. The methodology adopted was based in BOOT statistical approach. Five comparison statistics were calculated for three test points in order to find out the quality of the modelled results. Additionally, a hourly profile of predicted versus measured concentrations was developed.